Costos por órdenes de producción y su incidencia en la rentabilidad de la empresa Publicenter, cantón Valencia, provincia de los Ríos periodo 2022. - Cruz Mizalde, Génesis Eleonor (2024)
The present work was carried out to determine the costs by production orders and their relationship with profitability in the company “Publicenter” in the canton of Valencia during the period 2022, for this purpose a descriptive study was conducted, supported by a documentary and field bibliographic research for the collection of information. The data collection techniques were observation and interview. The instruments used were a cost matrix and the interview questionnaire applied to the owner of the microenterprise, and the financial statements of the company were also determined. A cost system by production orders was used, which was applied due to the nature of the production process, identifying the cost elements (raw material - labor, and IMC) in each of the production orders, and calculating the cost sheets that served as input to prepare the financial statements that were projected annually for decision making. The results of the horizontal and vertical analysis of the financial information showed a 12% decrease in assets and a 71% increase in liabilities, which, in general, represented a 15% decrease in total assets and equity. The vertical analysis showed an increase in non-current liabilities, with loans representing the largest % of total liabilities at 40%. The financial ratios were ROA of 66% and ROE of 82%. The company reports a net margin of 48% and an operating margin of 57%. It is concluded that after the analysis of the incidence of the production order costing system in the determination of profitability in the “Publicenter” company, it was determined that this system allows a more accurate allocation of the costs of the manufactured products, is profitable, and allows to have a profit.